L’anthropométrie au service du renforcement de la nation française : le cas de la promotion de la gymnastique par la médecine scolaire et militaire (fin xixe-début xxe siècle) - Elsie Mégret (Histoire, Médecine et Santé)
Based on the study of the works of two doctors who promoted school gymnastics, Louis Dufestel and Paul Godin, this article suggests that in terms of male health standards, the public health issue of combating tuberculosis intertwines with an ideology of perfecting bodies and the development of morphological criteria for conscription eligibility. It relies on historical literature from the late 19th and early 20th centuries concerning anthropometric practices and the strengthening of French youth, focusing particularly on chest measurement. After clarifying the role of anthropometry within school and military medicine, the article analyzes school gymnastics as a “corrective” practice that, supported by anthropometry, aims to prevent tuberculosis and strengthen the French nation. It then demonstrates how the measurement of the morphological correction induced by gymnastics is tailored for boys according to both physical and moral criteria for conscript selection.